DIPLOMASI BUDAYA KOREA SELATAN DAN IMPLIKASINYA TERHADAP HUBUNGAN BILATERAL KOREA SELATAN - INDONESIA - Leonardo Leonardo (Global Political Studies Journal, 2019)
This study aims to determine the extent to which the South Korean Cultural Diplomacy Bilateral and Implications South Korea-Indonesia. So the researchers tried to analyze the objectives, constraints, conditions before, after and the prospect of future conditions. The research method is qualitatively using descriptive analysis. Most of the data collected from interviews and literature as well as supported by the literature study and search the website. The study was conducted South Korean Cultural Center in Indonesia and the Embassy of Indonesia in South Korea. The results showed a change in the meaning of Hallyu before and after enforced as part of the South Korean diplomacy. From the 2005-2013 period the relationship between the two countries ever closer as facilitated by the cooperation in the field of culture. But now South Korea worried because in Indonesia began appearing parties that are difficult to accept the presence of Hallyu.